Desarrollo de un sistema de control de temperatura para una secadora experimental cilíndrica de cacao. - Guaquipana Rumiguano, Marlon Jesús (2023)
The lack of adequate temperature control by regulating the flow of air and gas in the cylindrical experimental dryer affects inefficient use of energy, inconsistency of drying and degradation of product quality. The cocoa drying process is an important step in its operation, as it helps reduce the humidity that is between 40 and 60% to a humidity of between 7 and 8%. For the drying process to be successful, it is essential to maintain an ideal temperature of 65 to 70 °C. A temperature control system is carried out using a PLC with a PID control, which is designed to automatically measure and adjust the temperature, determining whether it is necessary to increase or decrease the temperature according to the needs of the cocoa drying process. The system includes temperature sensors strategically placed within the dryer chamber, which continuously measure the temperature of the air heat flow, where these RTD PT-100 sensors send signals to a programmable logic controller (PLC S7-1200), which processes the information and makes the necessary adjustments. In addition to regulating the temperature, the control system includes notifications to alert through the use of an HMI screen where significant or dangerous deviations in temperature can be displayed, thus ensuring the safety of the process and avoiding damage to the product to be dried. By using the drying temperature control system, the following parameters are experimentally obtained: initial mass of cocoa is 45.36 kg, with a moisture content of 60%, the drying working temperature is 70 ° C, the LPG supply flow rate is 2 kg/h and the volumetric air flow rate is 127 3 h, completing the drying process, a final cocoa mass of 34.63 kg is obtained with a moisture content of 7.1% .